How Decisiveness, Self-Efficacy, Curiosity and Independent/Interdependent Self-Construals Are Related with Future Hopefulness among Senior Students - Öztekin, Remzi Hakan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Hope is a future oriented reasoning that influences psychological assets of individuals. A hopeful standing towards future can positively influence individual well-being. Different standings in terms of hopefulness may create variations on psychological assets of persons. In the current study, we examined the associations of decisiveness, self-efficacy, curiosity and self-construals with hopefulness. A total of 278 senior university students were recruited for the study from Eastern Mediterranean University in Famagusta, North Cyprus. Participants filled six questionnaires; Beck Hopelessness Scale, Independent and Interdependent Self-Construals Scale, Multi Domain Decisiveness Scale, Curiosity and Exploration Inventory II, Dispositional Hope Scale and General Self-Efficacy Scale. The data was analyzed by hierarchical multiple regression analysis on SPSS 23 software program. Results indicated that selfefficacy and decisiveness significantly predicted hopefulness, while curiosity did not predict hopefulness and only independent self-construal had the predictive effect on hopefulness. Based on these findings, emerging adulthood nature of study sample was discussed and further recommendations were presented. Keywords: Hopefulness, Self-Efficacy, Decisiveness, Curiosity, Emerging Adulthood, Self-construals.

ÖZ: Umut insanların gelecekle ilgili akıl yürütmelerini etkileyen psikolojik bir akıl yürütmedir. Geleceğe karşı umutlu bir tutuma sahip olmak kişinin iyilik halini olumlu yönde etkileyebilir. Farklı umutluluk dereceleri kişinin psikolojik durumunda değişkenliklere yol açabilir. Bu çalışmada gelecek yönelimli umudun kararlılık, öz yeterlilik, merak ve ilişkisel/bağımsız benlik yapıları ile olan ilişkisi incelenmiştir. Bu çalışmaya Kuzey Kıbrıs, Mağusa’da bulunan Doğu Akdeniz Üniversitesinden toplam 278 son sınıf öğrencisi çalışmaya dahil olmuştur. Katılımcılara 6 adet ölçek uygulanmıştır; Beck Umutsuzluk Ölçeği, Bağımsız ve İlişkisel Benlik Kurgusu Ölçeği, Çok Alanlı Kararlılık Ölçeği, Merak ve Keşfetme Envanteri II, Sürekli Umut Ölçeği ve Genel Öz-Yeterlilik Ölçeği. Toplanan veriler SPSS 23 programı aracılığıyla hiyerarşik çoklu regresyon analizi ile değerlendirilmiştir. Elde edilen sonuçlara göre, öz yeterlilik ve kararlılık umutlu olmayı yordamıştır. Merak umutluluk için bir yordayıcı role sahip değildir, ve sadece bağımsız ilişkisel benlik umutluluk halini yordamıştır. Bulgulardan yola çıkarak, kurulan bağlantılar ve katılımcıların beliren yetişkinlik dönemine dair özellikleri kapsamında tartışılmış, ilerideki araştırmalar için öneriler sunulmuştur. Anahtar Kelimeler: Umutluluk, Öz Yeterlilik, Kararlılık, Merak, Beliren Yetişkinlik, Benlik Yapıları.
Master of Science in Developmental Psychology. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Psychology, 2018. Supervisor: Assoc. Prof. Dr. Fatih Bayraktar.
Keywords: Psychology; Developmental Psychology; Emotions--Hope--Hopefulness--Psychology; Hopefulness; Self-Efficacy; Decisiveness; Curiosity; Emerging Adulthood; Self-construals